Penggunaan Buku Digital dalam Pembelajaran oleh Guru di MI Integral Al-Ukhuwwah - Rabi'ah Rabi'ah; Mardhiya Agustina (PT. Global Pustaka Ilmiah, 2025)
This study aims to describe teachers’ use of digital books at MI Integral Al-Ukhuwwah and to identify the benefits, challenges, and strategies applied in the teaching process. The research employs a qualitative descriptive approach, with primary data obtained through in-depth interviews with teachers who have used digital books in their teaching activities. The findings reveal that teachers employ a combination of printed and digital books to adapt to students’ needs and available facilities. Digital books are perceived to provide advantages such as accessibility, time efficiency, and enhanced teacher creativity in delivering materials. Nevertheless, several challenges remain, including technical issues like limited internet access and devices, as well as non-technical barriers such as digital skills and additional workload. To overcome these issues, teachers adopt various strategies, including self-learning, attending training sessions, and advocating for device procurement and network optimization. These findings highlight the importance of institutional support in enhancing teachers’ digital competence to ensure successful technology-based learning transformation.